Steer Clear: Analysis of New Zealand's Motor Vehicle Add-On Insurance Industry - Roche, Tomas (Victoria University of Wellington Law Review, 2023)
This article considers the current state of the motor vehicle add-on insurance industry in New Zealand in the light of the Commerce Commission's 2021 review of motor vehicle financing and add-ons. It suggests the current way the industry functions does not promote competition and facilitates several issues detrimental to consumers. The issues are the inadequacy of consumer awareness and understanding of add-on products (brought about by an insufficiency of information), a point of sales advantage enjoyed by providers of primary products, and an unsuitable dealer incentive system. These issues are producing negative consumer outcomes, as demonstrated by quantitative and qualitative industry evidence. The article considers how comparable jurisdictions, namely Australia and the United Kingdom, have corrected similar issues to increase consumer protection within their equivalent industries. It advocates similar industry reform for New Zealand. Industry reform should act in a preventative way to eliminate the creation of issues, as this best protects consumers. The primary reform that is recommended is the adoption of an industry-wide deferred sales model for add-on products.